Benefits and Challenges of Group Discussion as Creative Learning Strategies in Speaking Class - Rahmat, Hery; Jon, Roi Boy (Universitas Muhammadiyah Mataram, 2023)
Abstract: Creative learning strategy has turned out to be an important issue in foreign language learning. This article is aimed to investigate the benefits and challenges of group discussion as creative learning strategy to improve speaking’s proficiency. The research was conducted in an Islamic Senior High School. The research applied qualitative approach by using interviews and Focus-Group Discussions with 8 students as the source of data. Based on the analysis results, it was found that Group Discussion as creative learning strategy were beneficial during the speaking class because of it promote interaction and learning, motivation encouragement, and develop respect to another’s’ idea. Meanwhile, during the group discussion several issues arouse namely the individual learning preference, the problems with language aspects, and the students’ self-confidence. The research implies the significance of creative learning strategy to improve the English speaking successfully.